Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,370 questions

17,804 answers

1,438 comments

36,815 users

I need help solving this problem

0 votes
(x-y)^-2/(x^-2-y^-2)

 

asked Oct 27, 2014 in ALGEBRA 2 by doan12345 Pupil

1 Answer

+1 vote

The expression is (x-y)-2/(x-2-y-2).

= [1/(x - y)2] / (1/x2 - 1/y2)

= [1/(x - y)2] / [(y2 - x2)/x2y2]

= [1/(x - y)2] * [x2y2/(y2 - x2)]

= x2y2/(x - y)2(y2 - x2)

= x2y2/[(x - y)2(y - x)(y + x)]

= - x2y2/[(x - y)2(x - y)(x + y)]

= - x2y2/[(x - y)3(x + y)]

answered Oct 28, 2014 by casacop Expert

Related questions

asked Oct 24, 2014 in ALGEBRA 2 by anonymous
...